The future of nuclear energy and maritime power relations (Brazilian Journal of Radiation Sciences (BJRS), 2021)
Considering the presence of the nuclear issue in the main international forum and agenda as well as the increase in the visibility of the Brazilian Navy's Strategic Projects in the nuclear area, it is necessary to discuss the long-term aspects of this sector of capital importance for Brazil, which is likely to shape the country's development path in the next decades. This paper aims to propose a reflection on future environments concerning nuclear energy in which organs and sectors of Brazilian society (including Brazilian Navy) will act primarily in areas that have direct or indirect implications for maritime power and its interconnections with national development and international relations. This proposal includes discussing the prospective methods that will allow the reflection on the benefits of nuclear technology for Brazil and the international community, the technological challenges that are still facing for its effective implementation, and the possible revisions or redefinitions of formats for non-proliferation agreements. Issues to be addressed include the expansion of the uses of nuclear power and benefits can it provide to the future international community and to the maritime power; the changes that may occur in non-proliferation agreements. In environments of uncertainty and complexities, such as the nuclear area, the use of this methodology stimulates the interaction among the different involved parts, with its cultural, economic and social vision, taking part in defining the possible scenarios. Planners and leaders can gain exceptional ability to anticipate the actions that can drive the real world and produce potent insights.